(3ZfjI GdWGdHjfs - (3YHO GdbGOQ Hf CHj UGdM Hf YHO Gddg GdLjdGfj, CHh eMeO,J (B561 (3g` s ((3YfGjJ Hf hdi CMeO ZjGK s)
(3ChdgG (B:s
(3hHg fSJYjf bGd GdTjN GdMeO Gddg GdPi HJMeOg jJaJM cd cJGH CeG HYO abO GdM Ydi HYV GdGUMGH hTOO ai GdNWGH ai LeY gPG GdcJGH s
(3BNQgG (B:s
(3bjd eG GdaQV GdOGFe bGd GdUOb bjd EPG WdHJ Gddg HGdUOb CYWGc eQBI JHUQ ajgG cd TF ef YLGFH GdOfjG hGdBNQI Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdeLGejYs